2001
DOI: 10.1023/a:1013006515587
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Reaction pH can be used to select the preferred pegylation site chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…However, one exception is the inability to resolve by HPIEX the neighboring peaks of 5-kDa Lys 131 and 5-kDa Lys 164 , hence the lower purity estimation by analytical HPIEX relative to HPSEC. The HPIEX chromatography profiles and positional isomer elution order in this study matched those reported previously (12,15,19). In addition, the identity and purity of the purified positional isomers were confirmed by peptide mapping analysis.…”
Section: Confirmation Of Differential Activity Between 12-kda Monopegsupporting
confidence: 85%
See 4 more Smart Citations
“…However, one exception is the inability to resolve by HPIEX the neighboring peaks of 5-kDa Lys 131 and 5-kDa Lys 164 , hence the lower purity estimation by analytical HPIEX relative to HPSEC. The HPIEX chromatography profiles and positional isomer elution order in this study matched those reported previously (12,15,19). In addition, the identity and purity of the purified positional isomers were confirmed by peptide mapping analysis.…”
Section: Confirmation Of Differential Activity Between 12-kda Monopegsupporting
confidence: 85%
“…This procedure, previously utilized to resolve positional isomers of 12-kDa PEG-IFN-␣2b (15), was optimized to improve the resolution of positional isomers with varying PEG molecular weights. The purified mono-PEG-IFN-␣2b size exclusion pools were dialyzed overnight at 5°C against HPIEX buffer A (1.8 mM citric acid monohydrate, 3.3 mM sodium phosphate dibasic heptahydrate, pH 5.3).…”
Section: Production and Isolation Of Pegylated Interferon Isomers Formentioning
confidence: 99%
See 3 more Smart Citations